Enhanced deoxygenation performance and coke resistance of Ni-based catalysts for jatropha oil conversion by rare earth elements. (15th February 2023) - Yang, Huiru; Du, Xiangze; Zhou, Linyuan; Li, Dan; Hu, Changwei
Graphical abstract: Highlights: The coke resistance of Ni-based catalysts is improved profoundly by adding Er. 99.3 % deoxygenation ratio and 64.7 % yield of biofuels is achieved on Ni-Er/50S-Al. Er promotes the evenly distribution of Ni with smaller particle size. More surface oxygen vacancies are critical for deoxygenating JO when REEs added. The strong acidity leads to more coke form with Y added. Abstract: Herein, three kinds of rare earth elements (Ce, Er and Y) were added to Ni-based catalysts to regulate the deoxygenation ability and coke resistance towards jatropha oil (JO) conversion. Among them, the catalysts with lanthanide metals (Ce and Er) added exhibit positive effects. Conversely, the addition of Y is counterproductive. The one with Er added displays the best catalytic performance, achieving the highest deoxygenation ratio (99.3 %) and product yield (64.7 %), and the resultant biofuel has the highest calorific value (46.02 MJ/kg). The stability of the Ni-Er/50S-Al catalyst is significantly improved due to the enhanced coke resistance compared with the one without Er added. Smaller Ni particle sizes with better dispersion, higher amount of surface Ni 0 and surface oxygen vacancies are accomplished by adding Er, which contributes to the enhanced catalytic performance. The addition of Y weakens coke resistance, caused by strong acidity and big Ni particles. This study provides an effective idea for rationally designing catalysts with improved coke resistance and converting vegetable oils into biofuels.